IMI—The Dynamic Choroid: New Insights, Challenges, and Potential Significance for Human Myopia - Ostrin, Lisa A.; Harb, Elise; Nickla, Debora L.; Read, Scott A.; Alonso-Caneiro, David; Schroedl, Falk; Kaser-Eichberger, Alexandra; Zhou, Xiangtian; Wildsoet, Christine F. (Investigative ophthalmology & visual science, 2023)
The choroid is the richly vascular layer of the eye located between the sclera and Bruch's membrane. Early studies in animals, as well as more recent studies in humans, have demonstrated that the choroid is a dynamic, multifunctional structure, with its thickness directly and indirectly subject to modulation by a variety of physiologic and visual stimuli. In this review, the anatomy and function of the choroid are summarized and links between the choroid, eye growth regulation, and myopia, as demonstrated in animal models, discussed. Methods for quantifying choroidal thickness in the human eye and associated challenges are described, the literature examining choroidal changes in response to various visual stimuli and refractive error-related differences are summarized, and the potential implications of the latter for myopia are considered. This review also allowed for the reexamination of the hypothesis that short-term changes in choroidal thickness induced by pharmacologic, optical, or environmental stimuli are predictive of future long-term changes in axial elongation, and the speculation that short-term choroidal thickening can be used as a biomarker of treatment efficacy for myopia control therapies, with the general conclusion that current evidence is not sufficient.